2021
DOI: 10.3390/diagnostics11020157
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Allostasis: Using Bayesian Network Analytics to Explore and Evaluate Allostatic Markers in the Context of Aging

Abstract: Allostatic load reflects the cumulative strain on organic functions that may gradually evolve into overt disease. Our aim was to evaluate the allostatic parameters in the context of aging, and identify the parameters that may be suitable for an allostatic load index for elderly people (>60 years). From previously published studies, 11 allostatic (bio)markers could be identified that sustain sufficient variability with aging to capture meaningful changes in health status. Based on reported statistics (preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Previous studies have also established that allostatic load in patients with EH [19] without metabolic syndrome does not depend on patients' age and can be considered a general characteristic of EH [4]. Taking into account the pathogenetic links between allostatic load and aging [17,18,20,21,37,39,58,62], the increasing number of patients with EH [8,9,63], the possibility of using allostasis indicators to assess the effectiveness of therapy seems to be an urgent issue. The results of our study indicate that focusing only on target levels of BP does not provide an opportunity to reduce allostatic load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also established that allostatic load in patients with EH [19] without metabolic syndrome does not depend on patients' age and can be considered a general characteristic of EH [4]. Taking into account the pathogenetic links between allostatic load and aging [17,18,20,21,37,39,58,62], the increasing number of patients with EH [8,9,63], the possibility of using allostasis indicators to assess the effectiveness of therapy seems to be an urgent issue. The results of our study indicate that focusing only on target levels of BP does not provide an opportunity to reduce allostatic load.…”
Section: Discussionmentioning
confidence: 99%
“…It's important that the study involved patients receiving antihypertensive therapy that reached the target values. Taking into account the fact that the development of allostasis is commonly accompanied by aging of the body, this problem requires a more thorough investigation [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Allostatic load is measurable using an index of biomarkers known as the allostatic load index (ALI) in clinical studies. The ALI is composed of six categories: neuroendocrine function (cortisol, dehydroepiandrosterone, epinephrin, norepinephrine, dopamine, and aldosterone), immune function (IL-6, TNF-alpha, c-reactive protein, and IGF-1), metabolic function (HDL/LDL-cholesterol, triglyceride, glycosylated hemoglobin, blood glucose, insulin, albumin, creatinine, and homocysteine), cardiovascular/respiratory function (systolic blood pressure, diastolic blood pressure, peak expiratory flow, and heart rate), and anthropometric measurements (waist-to-hip ratio and body mass index) [ 136 , 137 ]. It is noteworthy that each allostatic mediator is interconnected in a nonlinear network, and many body systems are influenced by the same mediators [ 138 ].…”
Section: Homeostasis and Allostasis In Agingmentioning
confidence: 99%
“…Hence, the expression of IL-6 is proposed to serve as an early warning sign for the burden of multimorbidity [ 153 ]. As the level of IL-6 expression is included in ALI [ 136 ], analyzing ALI using the DNB theory will be fascinating to test as a novel methodology for the prediction of age-related loss of resilience, as well as the progression of cellular senescence in humans. Numerous studies have suggested that aging occurs through complex and dynamic changes [ 131 , 132 , 144 , 147 , 148 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Finally, because (visceral) obesity has convincingly been associated with a state of chronic low-grade inflammation, causing a significant strain on healthy immune functioning [19,20], it may, combined with the impact of chronic psychological stress on the immune system, very well close the toxic vicious circle of psychological stress, metabolic and cardiovascular health, and decreased inflammatory resilience [21] (see Figure 1). Glucocorticoids produced by the Hypothalamic-Pituitary-Adrenal (HPA)-axis seem to play a central role in this precarious equilibrium underlying health and well-being [22]. Consequently, effectively investing in cardiovascular fitness might stimulate some highly relevant positive side effects in immune functioning, either directly and/or indirectly via, for example, its effects on mental well-being.…”
Section: Introductionmentioning
confidence: 99%